The examination of immaterial capital in the hungarian LEADER local action groups - Kassai, Zsuzsanna; Áldorfainé Czabadai, Lilla (Studia Mundi – Economica, 2017)
International research results show that the EU LEADER program has a vital role in increasing the quantity of territorial capital in a region and improving the quality of its components and strengthening the relations among them. However, the characteristics of territorial capital of Hungarian LEADER regions have not been examined detailed in the current programming period yet. That is the reason why we study the main features of the immaterial components of territorial capital in the current LEADER program in our paper. We reveal the most important characteristics of human, social, relational and cultural capital of Hungarian Local Action Groups. The data of Hungarian Central Statistical Office were used for this analysis and multivariate statistical methods were applied to explore the similarities and differences between LEADER regions.